Direct marketing - Čičić Muris; Brkić Nenad (Marketing (Beograd. 1991), 2002)
Direct Marketing (DM) is usually treated as unworthy activity, with actions at the edge of legality and activities minded cheating. Despite obvious problems regarding ethics and privacy threat, DM with its size, importance and role in a concept of integrated marketing communication deserves respect and sufficient analysis and review